USE OF THE ISPRING PROGRAM IN THE ORGANIZATION OF IMMUNOLOGY CLASSES - Navruzova , S.A. ("Science Shine" International scientific journal, 2024)
This article highlights the benefits of using modern computer technologies, especially the ispring program, in the teaching of immunology.